2022
DOI: 10.1186/s12913-022-07896-5
|View full text |Cite
|
Sign up to set email alerts
|

Hospital utilization in Indonesia in 2018: do urban–rural disparities exist?

Abstract: Background The government must ensure equality in health services access, minimizing existing disparities between urban and rural areas. The referral system in Indonesia is conceptually sound. However, there are still problems of uneven service access, and there is an accumulation of patients in certain hospitals. The study aims to analyze the urban–rural disparities in hospital utilization in Indonesia. Methods The study used secondary data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
4
19
0
3
Order By: Relevance
“…Previous studies have shown that this condition is caused by living in rural areas, having limited access, and expensive transportation costs to reach high-quality health services. 18 - 21 The results of this study are in line with previous research that living in rural areas makes it possible not to participate in NHI. 7 , 22 …”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that this condition is caused by living in rural areas, having limited access, and expensive transportation costs to reach high-quality health services. 18 - 21 The results of this study are in line with previous research that living in rural areas makes it possible not to participate in NHI. 7 , 22 …”
Section: Discussionsupporting
confidence: 87%
“…The marital status of women is also important for determining the odds of facing barriers in healthcare access especially nancial resources which were mentioned as obtaining money in this study. Widowed, divorced, or separated women are more likely to face barriers to healthcare access and this nding was in line with previous studies in Malaysia 30 Indonesia 31 , and Tanzania 22 . The study in Ethiopia 20 using the 2016 Ethiopia DHS found that the likelihood of having perceived barriers to healthcare access among divorced or separated women was increased by 34% compared to women married or living together.…”
Section: Discussionsupporting
confidence: 91%
“…A positive psychology approach is essential in preventing health care professionals' burnout (Gómez-Salgado et al, 2019). Public hospitals are the main referrals for many patients from both urban and rural regions in Indonesia (Wulandari, Laksono, Nantabah, et al, 2022). Moreover, it has become Indonesia's leading choice of national health referral insurance system, especially for low-income societies (Pratiwi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%